The Effectiveness of the Family Hope Program (PKH) in Improving the Wellbeing of Elderly Beneficiaries in Tanjungsari Village, Indramayu Regency - Rachellia Ardhana; Hery Nariyah (Journal Of Social Science (JoSS), 2026)
The increasing number of elderly people in Indonesia presents significant challenges in ensuring their social and economic well-being, particularly for those who are economically vulnerable and have limited access to basic services. To address this issue, the government implemented the Family Hope Program as a social assistance initiative aimed at improving the quality of life of disadvantaged groups, including the elderly. This reserch aims to understand the effectiveness of monitoring the implementation of the Family Hope Program (PKH) in improving the well-being of the elderly in Tanjungsari Village, Karangampe Subdistrict, Indramayu Regency, as well as to identify the factors influencing the program’s success and the implementation challenges faced by the elderly. The research methodology involves a qualitative approach with a descriptive design, encompassing observation, data collection, data analysis, and conclusion analysis. The results of this study indicate that monitoring of the Family Hope Program (PKH) has been carried out with the support of the village government, which has had a positive impact on the well-being of the elderly, particularly regarding the fulfillment of economic needs. However, in its implementation, the program has not been fully successful due to a lack of understanding of the program and inaccuracies in data analysis. Additionally, physical constraints have hindered efforts to maintain health. Overall, the Family Hope Program (PKH) for the elderly in Tanjungsari Village is quite effective and capable of bringing about significant changes, but improvements are still needed in the areas of outreach, data collection, and health services to enhance its implementation